Analisis perbandingan kinerja keuangan perusahaan sebelum dan sesudah merger dan akuisisi pada perusahaan manufaktur yang listing di BEI 2009-2012 - Ulfathin Naziah; Yusralaini '; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to analyze the difference on firm performance before and after mergers and acquisitions a public company listed in Indonesia Stock Exchange. Corporate performance is measured by using financial ratio: Current Ratio, Total Asset Turn Over, Debt to Equity Ratio, Return on Assets, Return on Equity, Net Profit Margin dan Earnings per Share.The results showed that there is a difference between before and after the merger NPM, because the performance of the Company resulting from the merger and acquisition of NPM is not as good as the performance of the Company prior to mergers and acquisitions, the Company NPM result of mergers and acquisitions has decreased. There is a difference between ROA before and after the merger. Performance of the Company resulting from the merger and acquisition of ROA, the Company's performance improved after mergers and acquisitions, as ROA Company's results of mergers and acquisitions and increased significantly. There is a difference between before and after NPM Merger, the Company performance resulting from the merger and acquisition of ROE is not as good as the performance aspects of the Company prior to mergers and acquisitions, the Company's ROE for the results of mergers and acquisitions has decreased significantly. There is no difference between before and after the merger DER. Performance of the Company resulting from the merger and acquisition of aspects of the DER performance improved after company mergers and acquisitions. There is a difference between DR before and after the Merger, the Company performance resulting from the merger and acquisition of aspects of DR improved after mergers and acquisitions, as the Company DR result of mergers and acquisitions has increased significant improvement. There is a difference between EPS before and after the Merger Corporate Performance results of mergers and acquisitions from EPS aspects to improve after mergers and acquisitions, as the Company EPS result of mergers and acquisitions has increased significantly rise.There is no difference between before and after the Merger TATO Performance Company resulting from the merger and acquisition of the tattoo is not as good as the performance aspect of the Company prior to mergers and acquisitions, as the Company TATO result of mergers and acquisitions has increased significantly decrease. There is no difference between the CR before and after the Merger Corporate Performance results of merger and acquisition of the CR is not as good as the performance aspects of the Company prior to mergers and acquisitions, as the Company CR result of mergers and acquisitions has increased significantly decrease.Overall, the results of the Company There are differences in performance before and after mergers and acquisitions, due to performance results of mergers and acquisitions the Company experienced a significant increase.Keywords: Financial Performance, Merger and Akuisisi